The Role of Sentiment in the Economy of the 1920s - Ali Kabiri; Harold James; John Landon-Lane; David Tuckett; Rickard Nyman (Center for Economic Studies and Ifo Institute (CESifo), 2020)
John Maynard Keynes composed The General Theory as a response to the Great Crash and Great Depression with all their devastating consequences for the US macro economy and financial markets, as well as the rest of the world. The role of expectations his new theory set out has been widely accepted. The role of “animal spirits” he proscribed (i.e. the role of emotion in cognition) has remained much more controversial. We analyse over two million digitally stored news articles from The Wall St Journal to construct a sentiment series that we use to measure the role of emotion at the time Keynes wrote. An eight variable vector error correction model is then used to identify shocks to sentiment that are orthogonal to the fundamentals of the economy. We show that the identified “pure” sentiment shocks do have statistically and economically significant effects on output, money supply (M2), and the stock market for periods of the 1920s.
Keywords: D89; E32; E70; N10; N30; 330; Great Depression; general theory; algorithmic text analysis; behavioural economics